PERILAKU PEMILIH DALAM PEMILIHAN KEPALA DAERAH SERENTAK DI KABUPATEN ROKAN HULU TAHUN 2015 STUDI KASUS (DI KECAMATAN KEPENUHAN HULU) - Kadir "; Ali Yusri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Where election of regional head is used as a place of society to learn how real democracy and how to realize a good election of regional head for all parties, both win and lose. In this election In the election of Regional Head and Deputy Head of Region in Rokan Hulu Regency every candidate nominating is supported by their respective supporting parties. In the behavior of the people of subdistrict Kepenuhan Hulu, there are three theories: sociological approach, psychological approach and rational approach. The result of behavioral research of the people of districts is influenced in sociological approach because the people are choosing the ethnic candidate pair from the community using sociological approach. To find out the reason people do not choose the pair H. Syafaruddin Poti, because people are disappointed with the figure of H. Syafaruddin Poti less socialize with the community Kepenuhan Hulu Subdistrict, besides H. Syafaruddin Poti socialize less evenly, because H. Syafaruddin Poti only socialize in village Melayu.